Fluid management in hospitalized pediatric patients. (24th June 2022) - Alexander, Erin; Weatherhead, Jeffrey; Creo, Ana; Hanna, Christian; Steien, Dana B.
Abstract: The proper use of intravenous fluids has likely been responsible for saving more lives than any other group of substances. Proper use includes prescribing an appropriate electrolyte and carbohydrate solution, at a calculated rate or volume, for the right child, at the right time. Forming intravenous fluid plans for hospitalized children requires an understanding of water and electrolyte physiology in healthy children and how different pathology deviates from the norm. This review highlights fluid management in several disease types, including liver disease, diabetic ketoacidosis, syndrome of inappropriate antidiuretic hormone, diabetes insipidus, kidney disease, and intestinal failure as well as in those with nonphysiologic fluid losses. For each disease, the review discusses specific considerations, evaluations, and management strategies to consider when customizing intravenous fluid plans. Ultimately, all hospitalized children should receive an individualized fluid plan with recurrent evaluations and fluid modifications to provide optimal care.